Effects of dissolved Ca2+ and Mg2+ on passivity of UNS N08800 alloy in simulated crevice chemistries with and without Pb contamination at 300 °C. (November 2015) - Lu, B.T.; Tian, L.P.; Zhu, R.K.; Li, N.; Shi, S.Q.; Luo, J.L.
Highlights: Pb contamination degrades the passivity of alloy significantly. Ca 2+ and Mg 2+ in the Pb-free solutions at 300 °C reduce the stability of passive film. Ca 2+ and Mg 2+ in Pb-containing solutions reduce the detrimental impacts of Pb. The donor densities correlate with MOH bond in passive films and SCC susceptibility. Abstract: The effects of Ca 2+ and Mg 2+ on passivity of UNS N08800 alloy at 300 °C are experimentally investigated in simulated crevice chemistries. In the Pb-free solutions, the impacts of Ca 2+ and/or Mg 2+ are similarly detrimental, but less in extent, as those caused by Pb-contamination, as indicated by the increased passive current density, the lower breakdown potential, the promoted incorporation of hydrogen into the passive films and the formation of the films with highly defective structures containing more MOH bonds. However, when Ca 2+ and/or Mg 2+ are/is concurrently present with Pb cation, they mitigate the detrimental impact of lead on the passivity.